Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Pengeluaran Zakat Pada Bank Umum Syariah di Indonesia - Ais Oviyanda; Cut Delsie Hasrina; Isthafan Najmi; Azlim Azlim (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aims to determine the magnitude of the influence of profitability and firm size simultaneously on zakat expenditure in Islamic commercial banks in Indonesia. The data used in this study are secondary data and primary data obtained from the company's financial statements. The technique used as an analytical tool in this study is by using multiple linear regression analysis with the help of the SPSS version 23 program. In this study hypothesis testing was carried out using the t test which is a partial test and the F test which is a simultaneous test at a 95% confidence level. The results of the study show that profitability has an effect on zakat expenditure in Indonesian Islamic commercial banks with a β1 value of 0.507 with the calculation results of β1 ≠ 0 or the tcount value (4.971) is greater than the ttable value (1.995). Firm size has an effect on zakat expenditure at Indonesian Islamic commercial banks with a β2 value of 0.427 with the calculation results of β2 ≠ 0 or the tcount value (5.958) is greater than the table value (1.995). Profitability and company size simultaneously influence the issuance of zakat on Indonesian Islamic commercial banks with a Fcount value (26.012) greater than Ftable value (3.132). The coefficient of determination (R2) obtained with a value of 0.514 means that by 51.4% changes in the variable bond (zakat expenditure on Indonesian Islamic commercial banks) can be explained by changes in profitability, company size and company age. Meanwhile, the remaining 48.6% is explained by other factors outside the three variables described above, such as liquidity, company performance, stock prices and others.